Volume 8: Heat Transfer and Thermal Engineering 2017
DOI: 10.1115/imece2017-71384
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations to Study the Effect on Coefficient of Friction and Heat Transfer Coefficient in the Lubricants With Nano Blending

Abstract: Worm gears are unique in their ability to achieve large speed reductions in a compact space with gear ratios of 20:1, 60:1 and 200:1 or even higher in some cases and have transmission efficiency between 50% and 70%. One of the major drawback in worm drive design is the relative motion between the two mating elements is entirely sliding. This sliding motion continuously expels the lubricant aside leading to higher wear and increase in temperature. This phenomenon leads to high wear and higher temperatures, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Min-Sheng Liu et al [5], experimentally examined thermal conductivity of EG/CuO nanofluids and observed 22.4% enhancement in the thermal conductivity compared to the base fluids with 5 Vol%. ChilamkurtiLvrsv Prasad et al [6], experimentally studied heat transfer coefficient and the coefficient of friction of lubricants blended with Al 2 O 3 nanopowder and observed 46.35% increase in heat transfer coefficient and 16.85% reduction in coefficient of friction at room temperature (35°C) with 0.5Vol%. K. Y. Leong et al [7], conducted the experiments on car radiator using EG/Cu nanofluids with 0-2 Vol% range and observed that 3.8% of improvement in the heat transfer rate with the dispersion of 2% Cu nanopowder with Reynolds number of 5000 and 6000 for coolant and air respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Min-Sheng Liu et al [5], experimentally examined thermal conductivity of EG/CuO nanofluids and observed 22.4% enhancement in the thermal conductivity compared to the base fluids with 5 Vol%. ChilamkurtiLvrsv Prasad et al [6], experimentally studied heat transfer coefficient and the coefficient of friction of lubricants blended with Al 2 O 3 nanopowder and observed 46.35% increase in heat transfer coefficient and 16.85% reduction in coefficient of friction at room temperature (35°C) with 0.5Vol%. K. Y. Leong et al [7], conducted the experiments on car radiator using EG/Cu nanofluids with 0-2 Vol% range and observed that 3.8% of improvement in the heat transfer rate with the dispersion of 2% Cu nanopowder with Reynolds number of 5000 and 6000 for coolant and air respectively.…”
Section: Introductionmentioning
confidence: 99%